CHANGES OF MICROBIOTA-DERIVED SHORT-CHAIN FATTY ACID LEVELS IN CHILDREN WITH VIRAL DIARRHEA - Kerimova, A.A.; Gasangulieva, G.M.; Aliyeva, U.A.; Huseynova, A.B.; Namazova, B.A. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the clinical and diagnostic significance of changes in short-chain fatty acids levels in children of the first year of life with viral diarrhea. The study was conducted in 94 children with diarrhea aged 0–1 year. The control group consisted of 30 healthy children. Determination of short-chain fatty acids levels was conducted, using gas-liquid chromatography. According to results, in the mono variant of viral diarrhea, acetic acid decreased by 1.5 times compared to the, in mixed variants – by 1.8 times (p
Keywords: short-chain fatty acids; butyric acid; valerianic acid; microbiota; gastroenteritis